PELAKSANAAN PERJANJIAN PENGANGKUTAN PENUMPANG MENURUT UNDANG-UNDANG NOMOR 22 TAHUN 2009 - Marsidah, Marsidah (Solusi, 2018)
Communities that are still very dependent on public transport are not matched by the provision of adequate public transport. This causes passengers to use public transport services, sometimes less comfortable, so that the quality of transportation services is needed. In addition, the legal protection for all parties related to the transportation system, especially the users of transportation services is very important given the importance of the role of traffic and road transport for the whole community. The problem in this research is how the legal consequences arising in the implementation of the transport agreement according to Law Number 22 Year 2009 on Traffic and Road Transport. The type of research used in this writing is normative juridical. Legal consequences for transport service managers in the event of defaults on passengers in the operation of transportation which is their obligation so as to provide passengers with loss of goods that are legally registered and physically disabled for transportation service providers, the legal consequences for transport service managers must be responsible for paying obligations or compensation in accordance with applicable regulations. Legal protection for public transport passengers from public transport companies is responsible for all losses caused by the actions of people employed in transport activities such as the provisions of Article 191 and Article 192 paragraph (1) of Law Number 22 of 2009